KONSEP EFISIENSI USAHATANI PANGAN DAN IMPLIKASINYA BAGI PENINGKATAN PRODUKTIVITAS (Forum Penelitian Agro Ekonomi, 2016)
Basic problems for farm business improvement are lack of types, quantity, quality, and continuity of agricultural products supply in accordance with market demand dynamics. Improving agricultural productivity can be carried out through efficiency enhancement and technology breakthrough. Empirical studies on technical efficiency (TE) show that Indonesian farming TE values for some food commodities are moderate to high (0.50-0.80) suggesting that the food-crop farm business are not fully technically efficient.  Meanwhile, the allocative efficiencies (AE) of some food-crop farm businesses range from 0.45 to 0.70, and economic efficiencies (EE) vary from 0.35 to 0.60 indicating low to moderate efficiency levels. Socio-economic factors affecting the lower technical inefficiencies are: (a) land size, (b) household income, (c) formal education of household heads, and (d) household heads’ experience in farming. Strategies to improve farm business efficiency are through transformation of traditional farming to modern one In the future the farming should be driven by innovation in science and technology and skilled human resources.